Can the greater fool theory explain bubbles? Evidence from China - Xuan Zou (Rutgers University, Department of Economics, 2018)
Many have noticed the phenomenon that naive investors are attracted to the market as stock prices soar, yet few empirical studies have tested for this bubble phenomenon. This paper presents previously unused data on the aggregate number of newly opened brokerage accounts in China and tests the role of new investors in bubble formation. I find that new investors, attracted by soaring stock prices and the intensive trading activities of others, drove the Chinese stock market bubbles in 2007 and 2015, supporting the Greater Fool theory of bubbles. The inexperienced and naive new investors appear more likely to be the "greater fools." Using the residual orthogonalization method, I build a data-driven structural model system, where shocks from the new accounts variable explain 40-55% of Chinese stock return variation.
Keywords: G1; G12; G41; 330; bubble; individual investors; volume; Chinese stock market